Optimalisasi dan Evaluasi Jaringan Fiber Optik di Permukiman Desa - Ando Mulia Agung Hutabarat; Alex Wijaya; Timur Dali Purwanto (APTIKOM SUMSEL, 2025)
The rapid advancement of information and communication technology has significantly influenced business activities, particularly in rural areas. However, Desa Tanah Abang Utara remains categorized as a blank spot, where mobile communication services such as Global System for Mobile Communications (GSM) and other providers are not optimally available. This condition hampers internet access, limiting local businesses in utilizing digital platforms for marketing and sales. This study aims to implement a fiber optic (FO) network in Desa Tanah Abang Utara as a solution to improve internet connectivity. The research employs the Action Research method, which consists of five stages: diagnosing, action planning, action taking, evaluating, and learning. The installation process involves configuring routers, VLAN settings on switches, FO cable installation, and Optical Line Terminal (OLT) deployment. Network performance is evaluated using Wireshark software to measure key parameters such as throughput, latency, and packet loss. The results show that the implemented FO network significantly enhances internet access reliability, providing a stable and high-speed connection for the community. This improvement enables local businesses to leverage digital platforms for business expansion and enhances overall socio-economic development. The study highlights the importance of fiber optic networks in overcoming digital disparities in rural areas and serves as a reference for policymakers in developing telecommunications infrastructure in underserved regions.